Panhypopituitarism due to Absence of the Pituitary Stalk: A Rare Aetiology of Liver Cirrhosis - Marta Gonzalez Rozas; Lidia Hernanz Roman; Diego Gonzalez Gonzalez; José Luis Pérez-Castrillón (Case Reports in Endocrinology)
Studies have established a relationship between hypothalamic-pituitary dysfunction and the onset of liver damage, which may occasionally progress to cirrhosis. Patients with hypopituitarism can develop a metabolic syndrome-like phenotype. Insulin resistance is the main pathophysiological axis of metabolic syndrome and is the causal factor in the development of nonalcoholic fatty liver disease (NAFLD). We present the case of a young patient with liver cirrhosis of unknown aetiology that was finally attributed to panhypopituitarism.